Digested raspberries polyphenols for brain health: attenuation of neuroinflammation - Garcia, Gonçalo Filipe Rodrigues, 1990- (2017)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2014